Study on the characteristics of a homemade differential-velocity–type compliant joint for robotic manipulators - Jwu-Sheng Hu; Cheng-Hua Wu; Yi-Jeng Tsai; Chung-Hsien Kuo (Advances in Mechanical Engineering, 2015)
Design of a new differential-velocity–type compliant joint with two motors is proposed for robotic manipulators. The speed/output torque of the differential-velocity–type joint is synthesized by controlling the differential speeds of a pair of actuators. Descriptions of the design concept, theoretical analysis, and the experiments are presented in this article. The experimental results showed that (1) the stiffness of the differential-velocity–type joint can be regulated by changing the speeds of both motors, (2) the differential-velocity–type joint actually reduced 7.9%−15.7% time compared with the single-drive joint when performing five cycles of reciprocation, and (3) a new design of delta-type robot with differential-velocity–type driving modules was developed for verification. The experimental results showed that the differential-velocity–type delta robot can perform flexible assembly operations within a 0.028-mm tolerance.